Pastures of Heaven orchard - Kjysten Drew:::Creator::::::::::::
Pastures of Heaven/Las Pasturas del Cielo, looking down-valley at an Orchard. This photo accompanies text from Pastures of Heaven: 'After a long time a few families of squatters moved into the Pastures of Heaven and built fences and planted fruit trees.' Original is slide.